Dietary Cysteine Intake is Associated with Blood Glutathione Levels and Isometric Strength - Margaritelis, Nikos V.; Chatzinikolaou, Panagiotis N.; Bousiou, Flora V.; Malliou, Vasiliki J.; Papadopoulou, Sousana K.; Potsaki, Panagiota; Theodorou, Anastasios A.; Kyparos, Antonios; Geladas, Nikos D.; Nikolaidis, Michalis G.; Paschalis, Vassilis (International Journal of Sports Medicine, 2020)
Glutathione is the most abundant cellular antioxidant and regulates redox homeostasis. Healthy individuals with certain antioxidant inadequacies/deficiencies exhibit impairments in physiological functions. The aim was to investigate whether low levels of dietary cysteine intake are associated with a) lower erythrocyte glutathione, b) increased plasma F2-isoprostanes, and c) impaired muscle function. Towards this aim, we recorded the dietary intake of the three amino acids that synthesize glutathione (i. e., glutamic acid, cysteine, and glycine) in forty-one healthy individuals, and subsequently measured erythrocyte glutathione levels. Maximal isometric strength and fatigue index were also assessed using an electronic handgrip dynamometer. Our findings indicate that dietary cysteine intake was positively correlated with glutathione levels (r=0.765, p<0.001). In addition, glutathione levels were negatively correlated with F2-isoprostanes (r=− 0.311, p=0.048). An interesting finding was that glutathione levels and cysteine intake were positively correlated with maximal handgrip strength (r=0.416, p=0.007 and r=0.343, p=0.028, respectively). In conclusion, glutathione concentration is associated with cysteine intake, while adequate cysteine levels were important for optimal redox status and muscle function. This highlights the importance of proper nutritional intake and biochemical screening with the goal of personalized nutrition.
Keywords: antioxidants; cysteine; deficiency; exercise; glutathione; strength